Integrating Personal Moral Values in Teaching Literature in English as a Foreign Language Setting - Muzakki Afifuddin (Buletin Al-Turas, 2022)
PurposeThis paper aimed at exploring the existence of the integration of personal moral values within the process of the teaching of literature in English as a Foreign Language (EFL) setting in an Islamic University in Indonesia.MethodAs a part of the personal literary competence being performed in approaching literary texts, in this case study, literature instructors in EFL setting were seen as approaching the teaching of the English Literary texts through the framework of Borsheim-Black’s Critical Literature Pedagogy. It was a pedagogical framework for merging goals of critical literacy and canonical literature instruction consisting of two stances of reading literature: reading with the text and reading against the text.Results/FindingsIn this study, the stance of reading against the text became distinguishable since the findings showed that both literature instructors inadvertently articulated their personal moral values in approaching the teaching of English literary texts within the classroom although the objectives of the courses did not focus on teaching moral values.ConclusionThe study concluded that these instructors have a certain perception towards the integration of their personal moral values in the reading of literature and the teaching of literature in EFL setting. Hopefully, such assumption will be studied in further research.